Cultural analysis and sociology of culture in Greece, 1980-2014: literature review and a preliminary sociological interpretation - Δεμερτζής, Νίκος; Σουλιώτης, Νίκος; Μαρκατάς, Γιώργος (The Greek Review of Social Research, 2017)
The chapter presents a preliminary overview of cultural analysis and cultural sociology in Greece during the last three decades. The overview is based on a database including publications in these fields and basic biographic elements of their authors. We argue that the «cultural turn» fueled in our country a quite rich but at the same time scattered discussion in which clear «schools of thought» can be barely traced. Greek scholars put emphasis on the representation of main phenomena (among others: national identity, immigration, city) in the mass media and the mass/popular culture. They have been much less interested in other traditional issues of cultural sociology and sociology of culture like cultural production and consumption and cultural policy. As a result of scarce funding opportunities, research has been mainly small-scale and based on qualitative methods.